Evaluation of ventilation systems as a cooling strategy in dwellings using a validated TRNSYS model - Ícaro C. Vera Alves; Pedro J. Martínez Beltrán; Javier Molina González (Scientific Reports)
Abstract Free cooling is a passive technique in which ventilation is used to reduce the sensible heat load when outdoor conditions are favourable. This technique is easy to apply in residential buildings, as it can be implemented either naturally or via a mechanical system. However, one should not lose the main purpose of ventilation in buildings: to ensure indoor air quality (IAQ). To assess the applicability of this technique depending on the ventilation system (natural or mechanical), an experimentally validated TRNSYS model of the detached single-family dwelling La Casa de la Tierra, coupled with a natural ventilation model in CONTAM, was applied in case studies. As a novelty, both systems are integrated into the legislative framework of minimum ventilation requirements to ensure IAQ and comfort. The results indicated that combining both systems during summer days and nights provides a much more attractive solution than relying on a single system throughout the year. Furthermore, in addition to its straightforward implementation, the proposed solution ensures IAQ, with a reduction in ventilation energy consumption of up to 46.2% in summer and allows 6.3 times more climatic cooling potential to be harnessed.